Extracorporeal Membrane Oxygenation in the Treatment of Severe Pulmonary and Cardiac Compromise in Coronavirus Disease 2019: Experience with 32 Patients. Issue 7 (July 2020) - Jacobs, Jeffrey P.; Stammers, Alfred H.; St. Louis, James; Hayanga, J. W. Awori; Firstenberg, Michael S.; Mongero, Linda B.; Tesdahl, Eric A.; Rajagopal, Keshava; Cheema, Faisal H.; Coley, Tom; Badhwar, Vinay; Sestokas, Anthony K.; et al.
Abstract : As coronavirus disease 2019 (COVID-19) cases surge worldwide, an urgent need exists to enhance our understanding of the role of extracorporeal membrane oxygenation (ECMO) in the management of severely ill patients with COVID-19 who develop acute respiratory and cardiac compromise refractory to conventional therapy. The purpose of this manuscript is to review our initial clinical experience in 32 patients with confirmed COVID-19 treated with ECMO. A multi-institutional registry and database was created and utilized to assess all patients who were supported with ECMO provided by SpecialtyCare. Data captured included patient characteristics, pre-COVID-19 risk factors and comorbidities, confirmation of COVID-19 diagnosis, features of ECMO support, specific medications utilized to treat COVID-19, and short-term outcomes through hospital discharge. This analysis includes all of our patients with COVID-19 supported with ECMO, with an analytic window starting March 17, 2020, when our first COVID-19 patient was placed on ECMO, and ending April 9, 2020. During the 24 days of this study, 32 consecutive patients with COVID-19 were placed on ECMO at nine different hospitals. As of the time of analysis, 17 remain on ECMO, 10 died before or shortly after decannulation, and five are alive and extubated after removal from ECMO, with one of these five discharged from the hospital. Adjunctive medication in the surviving patients while on ECMO was as follows: four of five survivors received intravenous steroids, three of five survivors received antiviral medications (Remdesivir), two of five survivors were treated with anti-interleukin-6-receptor monoclonal antibodies (Tocilizumab or Sarilumab), and one of five survivors received hydroxychloroquine. Analysis of these 32 COVID-19 patients with severe pulmonary compromise supported with ECMO suggests that ECMO may play a useful role in salvaging select critically ill patients with COVID-19. Additional patient experience and associated clinical and laboratory data must be obtained to further define the optimal role of ECMO in patients with COVID-19 and acute respiratory distress syndrome (ARDS). These initial data may provide useful information to help define the best strategies to care for these challenging patients and may also provide a framework for much-needed future research about the use of ECMO to treat patients with COVID-19.